Preparation and evaluation of molecularly imprinted membrane of teicoplanin. Issue 45 (8th November 2018) - Yao, Ru; Yu, Zhen; Wu, Manman; Yu, Haining
Abstract : Synthesis of teicoplanin molecularly imprinted membranes and a novel enrichment method for rapid determination of teicoplanin. Abstract : A molecularly imprinted membrane (MIM) with teicoplanin (TE) as a template and other related material membranes (organic nylon microporous membranes, polyvinylidene fluoride (PVDF) membranes, and polypropylene membranes) as supports were synthesized for the selective absorption of TE. These membranes can be used for pretreatment of biological samples and rapid determination of TE. Our results showed that PVDF MIM exhibited the best selectivity among the other three synthesized membranes and therefore, it was used in this study. The performance of PVDF MIM was examined, including surface structure, adsorption capacity, desorption capacity, selective adsorption capacity, and recovery rate; the precision, stability, repeatability, linearity and recovery rate of this method were investigated at the same time. Clean-up and enrichment of samples by TE MIM were reliable.